Improving the Ability of Maharah Qiraah Class VII Through Busy Book Learning Media: Meningkatkan Maharah Qiraah Kelas VII Melalui Media Pembelajaran Busy Book - Makalunsenge, Firgiawan; Abu Samad, Musdelifa; Abdullah, Abdullah (ELOQUENCE : Journal of Foreign Language, 2024)
Background: Learning media plays an important role in learning Arabic. The use of appropriate learning media can increase students' interest and activeness in learning subject matter, especially in learning Arabic. In the current era of information technology development, the use of innovative learning media such as Busy books can be an effective alternative to improve the quality of learning. Purpose: The objectives of this Learning Media Development include, (1) Developing effective and interesting Busy book-based learning media to improve students' Arabic reading skills at MTs Nurul Yaqin, Gorontalo City, (2) Measuring the feasibility of Busy book-based learning media, the researcher hopes to improve students' ability to read Arabic sentences at MTs Nurul Yaqin, Gorontalo City. Method: This research uses research and development (R&D) methods. Research and Development Theory is a type of research used to produce products. The research and development steps carried out are adapted from the ADDIE (Analyze, Designe, Develop, Implement, and Evaluate) design. Results and Discussion: It was found that for the pre-test data of the implementation class, there were 30 samples with a minimum score of 10 and a maximum value of 50, while for the post test data of the implementation class, there were 30 samples with a minimum score of 60, a maximum value of 90. then it can be concluded that there is a difference between the results of the Pre-Test and Post-Test of the Implementation class. In other words, that there is an influence of the Busy Book method on Maharatul Qiraah of MTs Nurul Yaqin Students. Conclusions and Implications: Based on the results of the limited trial, there was a significant increase between students' pre-test and post-test scores after using busy book media. Thus, it can be concluded that the busy book method has a positive influence on the ability of Maharatul Qiraah of MTs Nurul Yaqin students.Berdasarkan hasil uji coba terbatas, terdapat peningkatan signifikan antara nilai pre-test dan post-test siswa setelah menggunakan media busy book. Dengan demikian, dapat disimpulkan bahwa metode busy book memiliki pengaruh positif terhadap kemampuan Maharatul Qiraah siswa MTs Nurul Yaqin.